Doporučení pro léčbu závislosti na tabáku - Králíková, Eva; Češka, Richard; Pánková, Alexandra; Štěpánková, Lenka; Zvolská, Kamila; Felbrová, Vladislava; Kulovaná, Stanislava; Zvolský, Miroslav (Vnitrni lekarstvi, 2015)
Tobacco dependence causes every sixth death in the Czech Republic and is associated with diseases of the whole body. Treatment of tobacco dependence should be a standard part of clinical care to the extent of time available--from brief intervention at each clinical contact with patients up to intensive treatment. It includes psycho-socio-behavioural support and pharmacotherapy. It should apply to all professions in clinical medicine--as recommended by WHO mainly doctors, nurses, pharmacists and dentists, and should be covered within health care systems. Economically, it is one of the most cost-effective interventions in medicine. In our population over 15 years about 30% smokes (about 2.2 million people), diagnosis F17 relates to approximately 1.75 million people (about 80% of smokers).
Keywords: Smoking Cessation; analýza nákladů a výnosů; Cost-Benefit Analysis; Humans; Tobacco Use Disorder; Czech Republic; odvykání kouření; poruchy vyvolané užíváním tabáku; lidé; Česká republika